Posttraumatic Stress Symptom Severity and Cognitive-Based Smoking Processes Among Trauma-Exposed Treatment-Seeking Smokers: The Role of Perceived Stress - Garey, Lorra (Addict Behav, 2016)
Trauma exposure and smoking co-occur at an alarmingly high rate. However, there is little understanding of the mechanisms underlying this clinically significant relation. The present study examined perceived stress as an explanatory mechanism linking posttraumatic stress symptom severity and smoking-specific avoidance/inflexibility, perceived barriers to smoking cessation, and negative affect reduction/negative reinforcement expectancies from smoking among trauma-exposed smokers. Participants were trauma-exposed, treatment-seeking daily cigarette smokers (n = 179; 48.0% female; M(age) = 41.17; SD = 12.55). Results indicated that posttraumatic stress symptom severity had an indirect significant effect on each of the dependent variables via perceived stress. The present results provide empirical support that perceived stress may be an underlying mechanism that indirectly explains posttraumatic symptoms relation to smoking-specific avoidance/inflexibility, perceived barriers to smoking cessation, and negative affect reduction/negative reinforcement expectancies among trauma-exposed smokers. These findings suggest that there may be clinical utility in targeting perceived stress among trauma-exposed smokers via stress management psychoeducation and skills training.